Fostering Active Learning Through Interactive Methods In English Language Teaching - Sokhiba Kholdarova (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
This article explores the integration of interactive methods as an effective pedagogical strategy to enhance language skills in English classrooms. Grounded in communicative language teaching principles, interactive approaches such as group discussions, role-play, peer collaboration, technology-based activities, and task-based learning were implemented to promote learner engagement and communicative competence. The findings reveal that students demonstrated notable improvement in fluency, vocabulary retention, and critical thinking skills when actively engaged in interactive tasks. Furthermore, interactive methods created a student-centered learning environment that encouraged participation, motivation, and confidence in using English for real-life communication. The study also highlights challenges such as time constraints, classroom management, and the need for adequate teacher training. Overall, the integration of interactive methods proved to be a valuable approach for fostering meaningful language learning and developing the four essential skills—listening, speaking, reading, and writing.